The Upper Limit of Luminol's Amphiprotism: The Crystal Structure of 5‐Ammonium‐2‐hydro‐1, 4‐phthalzinediol Sulfate(IV). Issue 3 (3rd February 2020) - Martin, Thomas; Fleissner, Juliane; Milius, Wolfgang; Breu, Josef
Abstract : Luminol is chemically sufficiently stable to be diprotonated at high proton concentrations as provided by concentrated sulfuric acid. The luminol dication (5‐ammonium‐2‐hydro‐1, 4‐phthalzinediol) sulfate was isolated as macroscopic single crystals and its structure was determined and refined from single‐crystal X‐ray data collected at 173 K [cell parameters: a = 8.3994(17) Å, b = 6.9985(14) Å, c = 17.486(4) Å, β = 90.85(3)°, V = 1027.8(4) Å 3, space group P 21 / c ]. The structure is comprised of layers stacked along the b axis. Intralayer interactions are accomplished by strong hydrogen bonds of three luminol dications to one central [SO4 ] 2– ion. Interlayer interactions are formed by weak hydrogen bonds of one luminol dication to two [SO4 ] 2– ions in the adjacent layers, respectively, and alternating sandwich and parallel‐displaced π‐π‐stacking of the 1‐hydropyridazine‐3, 6‐diol moieties of luminol dications in adjacent layers, respectively. Abstract :